Relationship Between Maternal Dietary Patterns and the Triple Burden of Malnutrition in Indonesian Families: A Complex Sample Cross-Sectional Study - Zulhadiman; Briawan, Dodik; Ekayanti, Ikeu (The Indonesian Institute of Science and Technology Research, 2025)
The triple burden of malnutrition (TBM), comprising undernutrition, overnutrition, and micronutrient deficiencies, remains a major nutritional challenge in Indonesia amid rapid economic growth and shifting dietary habits. This study aimed to analyze the prevalence of TBM and its association with maternal dietary patterns using data from 1,005 mother–child pairs in the 2023 Indonesian Health Survey. Complex sample logistic regression was applied to account for the multistage sampling design. The prevalence of TBM was 4.3%. In children, 16.6% were underweight, 21.3% stunted, and 21.7% anemic, while 51.4% of mothers were overweight or obese and 15.0% anemic. Maternal dietary patterns were significantly associated with TBM risk, whereby mothers who rarely or never consumed grilled or charred foods were more likely to belong to non-TBM families (AOR = 8.57; 95% CI: 1.43–51.29; p = 0.018), as were those with moderate consumption (AOR = 4.78; 95% CI: 1.09–20.98; p = 0.038). In contrast, rare consumption of meat, poultry, or fish products with preservatives (AOR = 0.13; 95% CI: 0.02–0.95; p = 0.043) and fruits or fruit-based products (AOR = 0.19; 95% CI: 0.06–0.61; p = 0.005) was associated with a higher likelihood of TBM. A non-linear association was observed for flavor enhancers, where moderate consumption was linked to lower odds of TBM (AOR = 0.33; 95% CI: 0.15–0.73; p = 0.006), whereas rare consumption increased the likelihood of belonging to non-TBM families (AOR = 2.79; 95% CI: 1.04–7.48; p = 0.041). Additionally, moderate consumption of fats and oils was positively associated with TBM risk (AOR = 2.94; 95% CI: 1.01–8.54; p = 0.047). In conclusion, maternal dietary patterns significantly influence TBM risk among Indonesian families.